18F-Fluorodeoxyglucose positron emission tomography computed tomography detection threshold in follicular lymphoma: A case report. Issue 47 (November 2017) - Péricart, Sarah; Martin-Blondel, Guillaume; Franchet, Camille; Hitzel, Anne; Brousset, Pierre
Abstract: Rationale: Follicular Lymphoma in situ is generally identified as reactive follicular hyperplasia in which some of the hyperplastic germinal centers are colonized by few lymphoma cells. These cells can be detected through their strong 18F-Fluorodeoxyglucose avidity. Patient concerns: We report the case of a 70 year-old patient with arthralgia, weight loss and chronic fever over two months. A paraneoplastic polymyalgia rheumatica was initially suspected on abnormal 18F fluoro-deoxyglucose positron emission tomography (PET) pictures in two inguinal lymph nodes with a standardized uptake value at 8.6 and 5.8. Diagnoses: The PET lymph nodes were removed and histological examination revealed subtle lymph nodes infiltration by follicular lymphoma in situ. The absolute number of the follicular lymphoma cells determined using virtual imaging and 3D reconstruction appeared very low with a total tumor cell volume estimated at around 0.026 mm 3 for one lymph node and 0.041 mm 3 for the other. Interventions: The patient has been treated by corticotherapy alone. Outcomes: A long-time follow-up should be highly suggested for this patient to avoid any risk of clinical progression to follicular lymphoma. Lessons: Our findings show that low amounts of follicular lymphoma cells in reactive germinal center may reach a threshold of hypermetabolism detectable with positron emission tomography imaging, suggesting that tumor microenvironment also accounts for such as strong fluoro-deoxyglucose avidity. Thus, a systematic immunohistochemistry with anti-BCL2 antibodies should be performed on PET positive lymph node with apparent normal morphological features.